Baseline health parameters of rhinoceros auklets (Cerorhinca monocerata) using serum protein electrophoresis, acute phase proteins, and biochemistry - Lee, Lisa K. F.; Hipfner, J. Mark; Frankfurter, Greg; Cray, Carolyn; Pearson, Scott F.; Fiorello, Christine; Clyde, Nikolas M. T.; Hudson, Sarah A.; Parker, Sarah E.; Stallknecht, David E.; Furst, Emmanuelle; Haman, Katherine H. (Frontiers in Veterinary Science, 2024)
Clinical metrics of baseline health in sentinel seabird species can offer insight into marine ecosystem dynamics, individual and population health, and assist in wildlife rehabilitation and conservation efforts. Protein electrophoresis is useful for detecting changes in acute phase proteins and immunoglobulin levels that may indicate subtle inflammatory responses and/or infectious disease. Serum biochemistry can highlight nutritional status, metabolic derangements, and organ injury and function. However, baseline values for such health parameters are largely unknown for many seabird species. Therefore, the objective of this study is to establish baseline clinical health reference intervals for serum protein electrophoresis, acute phase proteins including serum amyloid A and haptoglobin, and biochemistry parameters in the rhinoceros auklet (Cerorhinca monocerata). Although the rhinoceros auklet is a relatively common seabird, it is considered to be vulnerable to many anthropogenic and natural stressors. As such, it may be considered a key sentinel seabird species of the North Pacific. Establishing baseline health parameters for this species may provide key information relevant to ocean health issues or environmental stressors. From 2013-2019, 178 wild, apparently healthy breeding adult rhinoceros auklets were captured across four breeding colonies in British Columbia, Canada (Lucy Island, Pine Island, Triangle Islands, and SGang Gwaay) and from one colony in Washington, USA (Protection Island). Reference intervals were calculated for protein electrophoresis fractions and acute phase proteins (n=163), and serum biochemistry (n=35) following established guidelines by the American Society of Veterinary Clinical Pathology. Animals were also assessed for the presence of antibodies to the influenza A virus. Approximately 48% (70/147) of sampled birds were seropositive for influenza A virus, with a prevalence of 50% (6/12) in 2013, 75% (47/63) in 2014, and 24% (17/72) in 2019. This work provides clinical baseline health metrics of a key North Pacific sentinel species to help inform marine ecosystem monitoring, recovery, and rehabilitation efforts in the Pacific Northwest.